Pengaruh Komposisi Media Dasar pada Kultur Embrio Kelapa Kopyor (Cocos Nucifera L. var.kopyor) - Putri , Halida Adistya; Gustiningsih, Dini; Sholeh, M. Mahftuchin; Firdaus, Fahmi (Jurnal Biotek, 2025)
Kopyor coconut has the potential to be an export crop native to Indonesia. The low production of kopyor coconut in Indonesia occurs because kopyor coconut cannot germinate conventionally like an endosperm mutation. This is due to the food reserves in the form of fruit flesh in crumb condition (kopyor), so it cannot supply sufficient nutrients for the seed germination process. The only appropriate and effective germination method to obtain Kopyor coconut seeds is in vitro embryo culture. This study aimed to determine the composition of the best culture media types for the growth of Kopyor coconut embryos. The study was arranged using a non-factorial Completely Randomized Design with three levels of media types: M1: Y3 + BA 4 mg L-1. M2: De Fossard + BA 4 mg L-1, and M3: Modified Media (Macro and Micro: Eeuwens, Organic: De Fossard) + BA 4 mg L-1. The results of the study showed that in the germination phase, M1 media was an effective medium for the germination of coconut kopyor up to 16 MST, where there are embryos in phase 4/embryos that swell more (10 embryos) compared to M2 media (3 embryos) and M3 media (2 embryos). After evaluating the planting method, media composition, and replacement of ZPT, the dominant embryos experienced germination, where there were 30% of embryos in the modified media (M3) tended to be higher than other media treatments, but not significantly different